Cardiopulmonary examinations of athletes returning to high-intensity sport activity following SARS-CoV-2 infection. (14th October 2021) - Kiss, O; Babity, M; Konig, A; Zamodics, M; Gregor, Z S; Horvath, M; Kiss, A; Rakoczi, R; Juhasz, V; Dohy, Z S; Szabo, L; Lakatos, B; et al.
Abstract: : During the pandemic, several studies were carried out on the short-term effects of acute SARS-CoV-2 infection in athletes. As some cases of young athletes with serious complications like myocarditis or thromboembolism and even sudden death were reported, strict recommendations for return to sport were published. However, we have less data about athletes who have already returned to high-intensity trainings after a SARS-CoV-2 infection. Athletes underwent cardiology screening (personal history, physical examination, 12-lead resting ECG, laboratory tests with necroenzyme levels and echocardiography) 2 to 3 weeks after suffering a SARS-CoV-2 infection. In case of negative results, they were advised to start low intensity trainings and increase training intensity regularly until achieving maximal intensity a minimum of 3 weeks later. A second step of cardiology screening was also carried out after returning to maximal intensity trainings. The above mentioned screening protocol was repeated and was completed with vita maxima cardiopulmonary exercise testing (CPET) on running treadmill. If the previous examinations indicated, 24h Holter ECG recording, 24h ambulatory blood pressure monitoring or cardiac MR imaging were also carried out. Data are presented as mean±SD. Two-step screening after SARS-CoV-2 infection was carried out in 111 athletes (male:74, age:22.4±7.4y, elite athlete:90%, training hours:14.8±5.8 h/w, ice hockey players:31.5%, water polo players:22.5%, wrestlers:18.9%, basketball players:18.0%). Second screenings were carried out 94.5±31.5 days after the first symptoms of the infection. A 5% of the athletes was still complaining of tiredness and decreased exercise capacity. Resting heart rate was 70.3±13.0 b.p.m., During CPET examinations, athletes achieved a maximal heart rate of 187.3±11.6 b.p.m., maximal relative aerobic capacity of 49.2±5.5 ml/kg/min, and maximal ventilation of 138.6±31.2 l/min. The athletes reached their anaerobic threshold at 87.8±6.3% of their maximal aerobic capacity, with a heart rate of 93.3±3.7% of their maximal values. Heart rate recovery was 29.9±9.2/min. During the CPET examinations, short supraventricular runs, repetititve ventricular premature beats + ventricular quadrigeminy and inferior ST depression were found in 1–1 cases. Slightly higher pulmonary pressure was measured on the echocardiography in 4 cases. Hypertension requiring drug treatment was found in 5.4% of the cases. Laboratory examinations revealed decreased vitamin D3 levels in 26 cases, decreased iron storage levels in 18 athletes. No SARS-CoV-2 infection related CMR changes were revealed in our athlete population. Three months after SARS-CoV-2 infection, most of the athletes examined had satisfactory fitness levels. However, some cases of decreased exercise capacity, decreased vitamin D3 or iron storage levels, arrhythmias, hypertension and elevated pulmonary pressure requiring further examinations, treatment or follow-up were revealed. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): This project was supported by a grant from the National Research, Development and Innovation Office (NKFIH) of Hungary; The research was financed by the Thematic Excellence Programme of the Ministry for Innovation and Technology in Hungary, within the framework of the Therapeutic Development and Bioimaging programmes of the Semmelweis University